2017
DOI: 10.1002/asi.23893
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive modeling of age‐related differences in information search behavior

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The majority of research on IT adoption among aging populations primarily focuses on the perspectives of processing speed theory and resource theory. Previous studies have demonstrated that compared to younger generations, older adults exhibit reduced efficiency in cognitive functions such as memory retention, attention span, problem-solving abilities, comprehension skills, and decision-making capabilities (Phillips and Sternthal, 1977; Ghasemaghaei et al ., 2019; Karanam et al ., 2017; Zhang and Li, 2017). Hence, senior-age employees may encounter challenges when performing ICT-enabled tasks due to a decline in information-processing speed (Tams, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of research on IT adoption among aging populations primarily focuses on the perspectives of processing speed theory and resource theory. Previous studies have demonstrated that compared to younger generations, older adults exhibit reduced efficiency in cognitive functions such as memory retention, attention span, problem-solving abilities, comprehension skills, and decision-making capabilities (Phillips and Sternthal, 1977; Ghasemaghaei et al ., 2019; Karanam et al ., 2017; Zhang and Li, 2017). Hence, senior-age employees may encounter challenges when performing ICT-enabled tasks due to a decline in information-processing speed (Tams, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%